Sexual Dimorphism and Morphological Variation in the Populations of Akis costitubera Marseul (Coleoptera: Tenebrionidae) By Using a Geometric Morpho- metric Approach - Abd-Alaziz, Sara N.; Bataw, Ali A.; Elmabrouk, Tarig S. (Al-Mukhtar Journal of Sciences, 2019)
The present study was conducted to evaluate the differences related to area of males and females of Akis costitubera Marseul by using morphometric geometric technique. The study was accomplished by using photographic records of each individual in ventral views by using a CELES- TRON X-150 digital camera. A matrix of photographs for each view was constructed using the TpsUtil program. In each view, we used 26 homologous landmarks which were digitized in the TPSdig2 program. 30 males and 30 females individuals were collected, photographed, and 26 land- marks from ventral views were digitized. We used a multivariate analysis of morphological variation. The results revealed significant differences between male and female (P<0.005), and the surface area of females was larger than that for males. The study concludes that sexual dimorphism occurred in the population of A. costitubera Marseul where these differences raise the question of whether sexual dimorphism may be modulated by natural selection.